2022
DOI: 10.1002/fsn3.3077
|View full text |Cite
|
Sign up to set email alerts
|

Pyrus ussuriensis Maxim 70% ethanol eluted fraction ameliorates inflammation and oxidative stress in LPS‐induced inflammation in vitro and in vivo

Abstract: Pyrus ussuriensis Maxim (PUM) is a popular fruit among consumers, and also used as medical diet for dissolving phlegm and arresting cough. The present study aims to investigate the potential protective effect of P. ussuriensis Maxim 70% ethanol eluted fraction (PUM70) on lipopolysaccharide (LPS)‐induced alveolar macrophages and acute lung injury (ALI) in mice. A total of 18 polyphenol compounds were tentatively identified in PUM70 by mass spectrometry (MS) analysis. The results in vivo suggested that PUM70 tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Previous research has been conducted on pear germplasm resources using agronomic and quality traits ( Zheng et al, 2022 ; Wu et al, 2018 ; Niu et al, 2019 ; Gong et al, 2020 ), Relevant fruit research has found that there are many ascorbic acids, flavonoids, sugars, organic acids and minerals (K, P, Mg, Ca) and other bioactive substances that are beneficial to human health ( Hou et al, 2022 ; Li et al, 2018a ; Adhikary et al, 2020 ; Sun et al, 2021 ; Che, Yamaji & Ma, 2018 ). Both Chinese traditional medicine and international modern medicine believe that pears have an antioxidant effect and are capable of lowering blood pressure, moistening the lungs, resolving phlegm clearing heat and detoxification the body, Eating pears regular can help supplement the nutrition needed by the human body, and may even have medicinal value ( Wang et al, 2015 ; Li et al, 2014 ; Peng et al, 2023 ; Ogita et al, 2020 ; Bajwa et al, 2015 ). With the increased enthusiasm for healthy, sustainable food and the acceleration of farming technology the importance of pear cultivation as an industry has increased in many places ( Zhang, Zhang & Gao, 2012 ; Li et al, 2018b ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has been conducted on pear germplasm resources using agronomic and quality traits ( Zheng et al, 2022 ; Wu et al, 2018 ; Niu et al, 2019 ; Gong et al, 2020 ), Relevant fruit research has found that there are many ascorbic acids, flavonoids, sugars, organic acids and minerals (K, P, Mg, Ca) and other bioactive substances that are beneficial to human health ( Hou et al, 2022 ; Li et al, 2018a ; Adhikary et al, 2020 ; Sun et al, 2021 ; Che, Yamaji & Ma, 2018 ). Both Chinese traditional medicine and international modern medicine believe that pears have an antioxidant effect and are capable of lowering blood pressure, moistening the lungs, resolving phlegm clearing heat and detoxification the body, Eating pears regular can help supplement the nutrition needed by the human body, and may even have medicinal value ( Wang et al, 2015 ; Li et al, 2014 ; Peng et al, 2023 ; Ogita et al, 2020 ; Bajwa et al, 2015 ). With the increased enthusiasm for healthy, sustainable food and the acceleration of farming technology the importance of pear cultivation as an industry has increased in many places ( Zhang, Zhang & Gao, 2012 ; Li et al, 2018b ).…”
Section: Introductionmentioning
confidence: 99%